The necessity of living law in tax-law enforcement - Vdovichena, Lidiia (Theoretical and empirical scientific research: concept and trends: International scientific-practical conference/ Oxford, GBR, 2020)
The problem of finding ways to improve the mechanism of tax-law enforcement, determining its adequate model is, according to many scholars, really relevant, because adequate to the goals of social development and the corresponding state and legal reform changes the purpose of law enforcement and its possible form. This situation encourages change and the means to achieve it to increase the social value and effectiveness of legal institutions in order to implement effective legal regulation of public relations. Tax-law scholarship must adapt its paradigms and research techniques to this new reality. It must be prepared to study tax law less as a mechanical structure than as a market, where many intersecting negotiations take place.
Keywords: living law; tax-law enforcement; taxpayers; tax-legal relations